Cost-effectiveness of ultrasound-guided foam sclerotherapy, endovenous laser ablation or surgery as treatment for primary varicose veins from the randomized CLASS trial. Issue 12 (2nd October 2014) - Tassie, E; Scotland, G; Brittenden, J; Cotton, S C; Elders, A; Campbell, M K; Campbell, B; Gough, M; Burr, J M; Ramsay, C R
Abstract: Background: The treatment of patients with varicose veins constitutes a considerable workload and financial burden to the National Health Service. This study aimed to assess the cost-effectiveness of ultrasound-guided foam sclerotherapy (UGFS) and endovenous laser ablation (EVLA) compared with conventional surgery as treatment for primary varicose veins. Methods: Participant cost and utility data were collected alongside the UK CLASS multicentre randomized clinical trial, which compared EVLA, surgery and UGFS. Regression methods were used to estimate the effects of the alternative treatments on costs to the health service and quality-adjusted life-years (QALYs) at 6 months. A Markov model, incorporating available evidence on clinical recurrence rates, was developed to extrapolate the trial data over a 5-year time horizon. Results: Compared with surgery at 6 months, UGFS and EVLA reduced mean costs to the health service by £655 and £160 respectively. When additional overhead costs associated with theatre use were included, these cost savings increased to £902 and £392 respectively. UGFS produced 0·005 fewer QALYs, whereas EVLA produced 0·011 additional QALYs. Extrapolating to 5 years, EVLA was associated with increased costs and QALYs compared with UGFS (costing £3640 per QALY gained), and generated a cost saving (£206–439) and QALY gain (0·078) compared with surgery. Applying a ceiling willingness-to-pay ratio of £20 000 per QALY gained, EVLA had the highest probability (78·7 per cent) of being cost-effective. Conclusion: The results suggest, for patients considered eligible for all three treatment options, that EVLA has the highest probability of being cost-effective at accepted thresholds of willingness to pay per QALY. Abstract : Endovenous laser ablation most cost-effective